Professional ethics, professionalization, and regulation of pharmaceutical sales representatives: Analyzing the Costa Rican case - Arguedas Ramírez, Gabriela (2020)
The purpose of this essay is to present an argument in favor of a strong state regulation of sales representatives working for pharmaceutical companies, taking as an example the Costa Rican legislation, which can be used as part of a strategy to discourage the various incorrect practices that have created a climate prone to corruption in the relationship between prescribers and pharmaceutical companies. This regulation should include three basic mechanisms: (1) The professionalization of sales representatives as a legal requirement, (2) Affiliation to the pharmaceutical professional association in the country, as a mandatory requirement, (3) Creation of state laws or policies to regulate the conduct and practices of pharmaceutical sales representatives, including the necessary mechanisms for filing complaints about breach of such regulations and adequate penalties for both the sales rep and the company. These rules can go along with by transparency policies such as the Open Payments Act in the US, and international guidelines on the proper relationship between prescribers and pharmaceutical companies, such as those published by the WHO.